The gender-sensitive spectrum of neurodevelopmental disorders: a case report on a ZMYM3 variant in a 19-year-old female - Alberto Cordella; Silvia Beatrice Maitz; Daniela Distefano; Marianna Lissi; Lucia Morellini; Leonardo Sacco; Leonardo Sacco; Leonardo Sacco (Frontiers in Psychiatry)
BackgroundNeurodevelopmental disorders (NDDs) such as Intellectual Disability, Autism Spectrum Disorder (ASD), and Attention-Deficit/Hyperactivity Disorder (ADHD) impact cognitive, behavioral, and social functions. The Zinc finger MYM-type protein 3, located on the X-chromosome, has been implicated in neurodevelopment, but its effects in females remain poorly understood due to limited research.Case presentationWe report a 19-year-old female with a de novo heterozygous variant in ZMYM3 (NM_201599.3:c.1927C>G, p.(His643Asp)), presenting with ADHD symptoms, poor motor coordination, and mild cognitive impairments. Although her language development was normal, she exhibited motor delays, learning and social difficulties, leading to anxiety and academic struggles. Neuropsychological assessment revealed an IQ of 85, with significant deficits in working memory and visuospatial reasoning but relative strengths in verbal comprehension. Brain MRI showed an incomplete left-sided hippocampal inversion. Genetic analysis confirmed the presence of the ZMYM3.Discussion and conclusionThis case contributes to the limited literature on ZMYM3-related NDDs in females, highlighting potential variability in phenotypic expression due to X-inactivation and penetrance effects. The patient’s symptoms emphasize how ADHD and other neurodevelopmental traits may manifest differently in females, often with more subtle and internalized features. Our findings underscore the importance of sex-specific research on ZMYM3-associated disorders and the need for comprehensive genetic and neuropsychological assessments to guide diagnosis and intervention in affected individuals.